Low cost carriers and the evolution of the US airline industry - Kai Hüschelrath; Kathrin Müller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
The article studies the evolution of the U.S airline industry from 1995 to 2009 using T-100 traffic data and DB1B fare data from the U.S. Department of Transportation. Based on a differentiation in market size and major players, entry and exit, concentration, fares, service, costs and profits, the article provides a fresh look on recent developments in the structure, conduct and performance of the domestic U.S. airline industry in light of both the substantial growth of low cost carriers and severe internal and external shocks such as merger and bankruptcy activity or the recent recession. Unlike previous studies, a consistent split of the analysis in network carriers and low cost carriers is introduced. In general, we find that the competitive interaction between network carriers and low cost carriers increased substantially throughout the last decade and must be considered as the main driver of competition in the domestic U.S. airline industry.
Keywords: L40; L93; 330; Airline industry; deregulation; network carrier; low cost carrier; Luftverkehrsgesellschaft; Passagierluftfahrt; Wettbewerb; Niedrigpreisstrategie; Branchenentwicklung; USA